2018
DOI: 10.1080/10926771.2018.1446480
|View full text |Cite
|
Sign up to set email alerts
|

Walking the Walk or Just Talk?: A Global Examination of Men’s Intentions to Take Violence Preventative Action

Abstract: Given the increasing prominence of both bystander-based approaches to gender-based violence (GBV) prevention and of proactively engaging men and boys to join efforts to end GBV, understanding the factors that support men's anti-violence bystander behavior is important. This study examined correlates of willingness to engage in violence preventative bystander behavior in a global sample of 299 adult men engaged in GBV prevention events or work. Participants came from over 50 countries and provided data via an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Whilst the benefit of the bystander approach is that all participants are engaged as proactive bystanders to address GBV (Katz, 2018), it is particularly important to engage men as bystanders as they often hold positions of power, can influence culture and can advocate for change (Our Watch, 2020). A global study of almost 300 men engaged in antiviolence work found that bystander willingness was supported with self-efficacy to engage in bystander behaviour, positive beliefs about the contributions of antiviolence involvement and an awareness of male privilege (Casey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the benefit of the bystander approach is that all participants are engaged as proactive bystanders to address GBV (Katz, 2018), it is particularly important to engage men as bystanders as they often hold positions of power, can influence culture and can advocate for change (Our Watch, 2020). A global study of almost 300 men engaged in antiviolence work found that bystander willingness was supported with self-efficacy to engage in bystander behaviour, positive beliefs about the contributions of antiviolence involvement and an awareness of male privilege (Casey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The descriptions of men’s experiences revealed a relationship between taking responsibility via personal morals/ethics and direct confrontation of men’s behavior, illuminating how men’s recognition of gender inequities, or social justice motivations, may result in confronting contradictory norms in their peers (Casey et al, 2018). If bystanders experience a positive response from female friends who avoided victimization as a result of intervention, it is perhaps unsurprising that men’s discussion of intervention opportunities were primarily of this type, as intervening with a potential perpetrator may result in a negative response (Moschella et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Men have been found to report weaker prosocial intentions, and, in some cases, less prosocial intervention behaviors, compared with women (Brown et al, 2014;Hoxmeier, Acock, et al, 2017;Hoxmeier, McMahon, et al, 2017;Moschella, Bennett, & Banyard, 2018). There is great need to understand the bystander intervention model in the context of primary prevention of sexual violence (DeGue et al, 2014;McMahon & Farmer, 2011), where men can play a critical role (Berkowitz, 2002;Casey, Allen, Tolman, Carlson, & Leek, 2018;Gidycz, Orchowski, & Berkowitz, 2011). Increasingly, research shows that men do not intervene as often, or across the spectrum of violence, to the same degree as women (Brown et al, 2014;Hoxmeier, Acock, et al, 2017;Hoxmeier, McMahon, et al, 2017;Moschella et al, 2018).…”
Section: Men As Bystanders To Sexual Violence Risksmentioning
confidence: 99%
See 2 more Smart Citations